Additive interactions of unrelated viruses in mixed infections of cowpea (Vigna unguiculata L. Walp) - Nsa, Imade Y.; Kareem, Kehinde T. (Frontiers in Plant Science, 2015)
This study was carried out to determine the effects of single infections and co-infections of three unrelated viruses on three cowpea cultivars (one commercial cowpea cultivar "White" and 2 IITA lines; IT81D-985 and TVu76). The plants were inoculated with Cowpea aphid-borne mosaic virus (CABMV), genus Potyvirus, Cowpea mottle virus (CMeV), genus Carmovirus and Southern bean mosaic virus (SBMV), genus Sobemovirus singly and in mixture (double and triple) at 10, 20 and 30 days after planting (DAP). The treated plants were assessed for susceptibility to the viruses, growth and yield. In all cases of infection, early inoculation resulted in higher disease severity compared with late infection. The virus treated cowpea plants were relatively shorter than buffer inoculated control plants except the IT81D-985 plants that were taller and produced more foliage. Single infections by CABMV, CMeV and SBMV led to a complete loss of seeds in the three cowpea cultivars at 10DAP; only cultivar White produced some seeds at 30DAP. Double and triple virus infections led to a total loss of seeds in all three cowpea cultivars. None of the virus infected IITA lines produced any seeds except IT81D-985 plants co-infected with CABMV and SBMV at 30DAP with a reduction of 80%. Overall, the commercial cultivar "White" was the least susceptible to the virus treatments and produced the most yield (flowers, pods and seeds). CABMV was the most aggressive of these viruses and early single inoculations with this virus resulted in the premature death of some of the seedlings. The presence of the Potyvirus, CABMV in the double virus infections did not appear to increase disease severity or yield loss. There was no strong evidence for synergistic interactions between the viruses in the double virus mixtures.